Penggunaan Media Sosial Memediasi Pengaruh Literasi Keuangan dan Gaya Hidup Hedonis Terhadap Perilaku Konsumtif (Business and Accounting Education Journal, 2022)
This study aims to examine and analyze the effect of financial literacy and hedonic lifestyle on consumptive behavior through the use of social media. The unit of analysis in this study is the consumptive behavior of Economic Education students at the State University of Semarang in 2017. In this study, the entire population was used as the unit of analysis. The data collection method in this study used a questionnaire. The data analysis technique used is descriptive analysis, regression analysis, path analysis and sobel test. The results showed that: 1) financial literacy and use of social media had no significant effect on consumptive behavior, 2) hedonic lifestyle had a positive and significant effect on consumptive behavior, 3) financial literacy had no significant effect on social media use, 4) hedonic lifestyle. positive and significant effect on the use of social media, 5) the use of social media cannot mediate the effect of financial literacy and hedonic lifestyle on consumptive behavior.